Into the purple zone: deconstructing the politics/administration distinction - Alford, John et al (2017)
We add new data to the long-standing debate about the interface between politics and administration, deploying theory and evidence indicating that it varies. It can be either a ?purple zone? of interaction between the red of politics and the blue of administration, or a clear line. We use survey responses from 1,012 mostly senior public managers in the United Kingdom, Australia, and New Zealand, along with semi-structured interviews with 42 of them, to examine the extent to which public managers perceive that they ?cross? the line or go into a zone, and the ways in which they do so. Our inclusion of a zone as well as a line recasts how roles and relationships between politicians and administrators can be conceived. Moreover, it raises questions about how particular contingencies affect whether public managers perceive and work with a line or a zone. - Reproduced.
Keywords: Political management; Politics - Administration dichotomy; Public administration